2019
DOI: 10.1159/000501939
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Patients with Gastric Superficial Neoplasia and Risk Factors for Multiple Lesions after Endoscopic Submucosal Dissection in a Western Country

Abstract: <b><i>Background:</i></b> Endoscopic submucosal dissection (ESD) is a treatment for early gastric neoplasms that preserves the stomach. However, the risk of multiple lesions persists. <b><i>Objectives:</i></b> To assess clinicopathologic characteristics of patients with early gastric neoplasms in a Western country and evaluate risk factors for multiple gastric lesions, synchronous, or metachronous. <b><i>Methods:</i></b> A retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…After a curative ER, the risk of LNM is low or very low, but there is a very low risk of recurrence and a moderate risk of metachronous lesions during follow-up (10 %-20 %) [192,[225][226][227][228][229][230][231]. There is evidence that Helicobacter pylori eradication decreases the risk of metachronous lesions and thus eradication is recommended if the patient has active H. pylori infection [232].…”
Section: Stomachmentioning
confidence: 99%
See 1 more Smart Citation
“…After a curative ER, the risk of LNM is low or very low, but there is a very low risk of recurrence and a moderate risk of metachronous lesions during follow-up (10 %-20 %) [192,[225][226][227][228][229][230][231]. There is evidence that Helicobacter pylori eradication decreases the risk of metachronous lesions and thus eradication is recommended if the patient has active H. pylori infection [232].…”
Section: Stomachmentioning
confidence: 99%
“…There is evidence that Helicobacter pylori eradication decreases the risk of metachronous lesions and thus eradication is recommended if the patient has active H. pylori infection [232]. No other strategies showed benefit in decreasing risk of metachronous lesions, but there is consistent evidence that older patients and patients with synchronous or multiple lesions at diagnosis and/or with extensive preneoplastic conditions are at higher risk [192,[225][226][227][228][229][230][231]. However, to date there are no data showing that these risk factors should influence surveillance intervals.…”
Section: Stomachmentioning
confidence: 99%
“…The presence of synchronous gastric lesions was the only independent risk factor for the occurrence of MGL in our study; at 3 years of follow-up, 30 % of the patients with synchronous lesions developed MGLs. Evidence estimates that one third of synchronous gastric lesions are only detected during the first follow-up endoscopy [33]. This highlights the need for full inspection of the entire gastric mucosa at the index examination even if one lesion has already been identified, as well as the need for surveillance in the first months after ESD.…”
Section: Progression Function Censoredmentioning
confidence: 99%
“…However, SDSGIM did not demonstrate predictive ability for malignancies with multiple lesions. Gisela Brito-Gonçalves et al [ 22 ] reported a trend for patients with extensive GIM (EGGIM > 4) who had a higher risk of multiple lesions. The trend was not found significant using multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%